Analisis Tingkat Pemahaman Siswa Terhadap Nilai-Nilai Pancasila dalam Pembelajaran Daring di SMPN 1 dan 2 Kecamatan Trowulan Kabupaten Mojokerto - Febiana Wahyuni Fauziyah; Warsono Warsono (Kajian Moral dan Kewarganegaraan, 2023)
Abstract This study aims to determine the level of student understanding of Pancasila values ​​in online learning for students at SMPN 1 Trowulan and students at SMPN 2 Trowulan, Trowulan sub-district, Mojokerto Regency, East Java. The type of research applied here is descriptive quantitative with the sampling technique using simple random sampling. The sample used in this study were students of class VIII C from SMPN 1 Trowulan and class VIII F students from SMPN 2 Trowulan. Collecting data by using an objective test for measure the level of understanding students to the values of Pancasila which then given to students. This research is based on Anderson dan Krathwohl taxonomy and information processing theory. The result of this research is known that is the level of understanding students perception of Pancasila values in online learning at SMPN 1 Trowulan and SMPN 2 Trowulan, Mojokerto Regency is at a very low predicate. This is evidenced by the highest percentage obtained from each school from SMPN 1 Trowulan, the largest percentage is 64% which is in a very low predicate. SMPN 2 Trowulan the largest percentage obtained was 48% in the predicate very low. Then, from SMPN 1 Trowulan it is known that there are a total of 85% of students who still do not meet the Minimum Completeness Criteria (KKM). Meanwhile, from SMPN 2 Trowulan, it is known that there are a total of 69% of students who still do not meet the Minimum Completeness Criteria (KKM). Keywords: Understanding, Pancasila Values, Online Learning